A digital marketing plan for Dona Laranja: creating a new juice brand using social media - Genú, Gustavo Henrique Gontijo (2022)
Dona Laranja - Organização de Produtores de Citrinos Lda started producing over 30 years ago, in the Algarve, in Quinta da Lameira, and developed to concentrate the supply and placement of the citrines production of its members, in order to enhance openness in international markets. Our main objective is to be associated with our customer for the best quality, at an excellent price. It aims to be present in a broad spectrum of countries, always ensuring a sweet and juicy product. We intend to establish regular customers who value its offer and increase the number of orders at Quinta da Lameira's production. The company has the objective to produce and sell a new juice brand, to be registered in the highest standards of production. Our family business management is based on unique experience and determination to create a product with added value for customers. The dynamism of its entire team allows it to upgrade our agricultural practices continually. Another critical success factor our company has, is our distribution system developed to reduce costs and increase delivery speed In this master thesis we focused in create a digital marketing plan with an external, internal and competitive analysis and implementation proposal. This implementation proposal consists on the development of the marketing strategy (strategic options: segmentation, targeting and positioning) and operational plan. The operational plan is the set of recommendations in terms of the marketing-mix: product, price, place and promotion.